2013
DOI: 10.1007/s11033-013-2894-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of 677C→T polymorphism a single substitution in methylenetetrahydrofolate reductase (MTHFR) gene in North Indian infertile men

Abstract: Failure or severe difficulty in conceiving a child is surprisingly common, worldwide problem. Half of these cases are due to male factors with defects in sperm (1 in 15 men) being the single most common cause. Also about 60-75 % of male infertility cases are idiopathic, since the molecular mechanisms underlying the defects remain unknown. DNA methylation is crucial for spermatogenesis and high methylenetetrahydrofolate reductase (MTHFR) activity in adult testis than other organs in mouse, signifies its critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Previous epidemiological studies have suggested ethnicity as a factor, where only certain ethnic populations revealed an association between this SNP and male infertility (Gupta et al, 2011;Chellat et al, 2012;Naqvi et al, 2014;Gong et al, 2015). The men in this study, however, were not evaluated for ethnicity.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Previous epidemiological studies have suggested ethnicity as a factor, where only certain ethnic populations revealed an association between this SNP and male infertility (Gupta et al, 2011;Chellat et al, 2012;Naqvi et al, 2014;Gong et al, 2015). The men in this study, however, were not evaluated for ethnicity.…”
Section: Discussionmentioning
confidence: 80%
“…A total of eight samples from fertile men, eight with moderate (5-15 million spermatozoa/mL), 20 with severe (1-5 million spermatozoa/mL), and eight with very severe (<1 million spermatozoa/mL) oligozoospermia were analyzed. PCR amplification was carried out in 25 lL reactions: 0.625 U HotStarTaq DNA polymerase (Qiagen), 19 PCR Buffer (Qiagen), 0.2 mM dNTPs, 0.5 lM forward and reverse primers (Naqvi et al, 2014), and 250-300 ng of DNA. The following cycling conditions were used: 95°C for 15 min; 44 cycles of 95°C for 45 sec, 65°C for 1 min, and 72°C for 1.5 min; and a final extension of 72°C for 5 min.…”
Section: Mthfr C677t Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have evaluated the association of MTHFR gene polymorphism with male infertility [13, 38-40, 22, 27, 17, 16, 18, 29, 25, 41, 28, 42, 26, 21, 23]. The MTHFR C677T polymorphism was reported to be associated with male infertility in the German [42], Indian [26,18,17,38], Korean [23], Chinese [19] and Italian populations [41]. In contrast, Stuppia et al [28] and Ebisch et al [21] did not find any statistically significance of C677T variation in infertile men from Italy and the Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 24 case-control articles (Bezold et al, 2001;Ebisch et al, 2003;Stuppia et al, 2003;Park et al, 2005;Lee et al, 2006;Paracchini et al, 2006;A et al, 2007;Dhillon et al, 2007;Sun et al, 2007;Ravel et al, 2009;Singh et al, 2005Singh et al, , 2010Gava et al, 2011;Liu, 2011;Qiu et al, 2011;Safarinejad et al, 2011;Eloualid et al, 2012;Vani et al, 2012;Karimian and Colagar, 2014;Li et al, 2014a,b;Mfady et al, 2014;Naqvi et al, 2014;Ni et al, 2015) were included in this meta-analysis. There were 21 studies of C677T with 4505 cases and 4024 controls, and 13 studies of A1298C with 2785 cases and 3094 controls.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%